2001
DOI: 10.1152/ajplung.2001.280.5.l947
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil defensins mediate acute inflammatory response and lung dysfunction in dose-related fashion

Abstract: High concentrations of neutrophil defensins from airway and blood have been reported in patients with inflammatory lung diseases, but their exact role is unclear. We investigated the direct effect of defensins on the lungs of mice. Intratracheal instillation of purified defensins (5-30 mg/kg) induced a progressive reduction in peripheral arterial O(2) saturation, increased lung permeability, and enhanced the lung cytochrome c content. These indexes of acute lung dysfunction were associated with an increased to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 38 publications
1
89
0
Order By: Relevance
“…Similarly, an excessive production of mucins causes clogging of the CF airways due to the accumulation of material that cannot be efficiently removed by the mucociliary clearance mechanism. Finally, the concentration of defensins in CF sputum/fluid could be so high as to be cytotoxic to airway epithelial cells (37)(38)(39). In sum, we provide evidence that flagellin, a potent virulence factor, strongly up-regulates the expression of matrilysin in lung epithelial cells and that this host enzyme is an early marker of bacterially induced inflammation.…”
Section: Resultsmentioning
confidence: 76%
“…Similarly, an excessive production of mucins causes clogging of the CF airways due to the accumulation of material that cannot be efficiently removed by the mucociliary clearance mechanism. Finally, the concentration of defensins in CF sputum/fluid could be so high as to be cytotoxic to airway epithelial cells (37)(38)(39). In sum, we provide evidence that flagellin, a potent virulence factor, strongly up-regulates the expression of matrilysin in lung epithelial cells and that this host enzyme is an early marker of bacterially induced inflammation.…”
Section: Resultsmentioning
confidence: 76%
“…16 Intratracheal instillation of a-defensins in mice leads to acute lung inflammation and dysfunction involving neutrophil influx and elastase release. 17 The a-defensins have a cytotoxic effect, induce IL-8 and IL-1b gene expression, IL-8 protein production and NF-kB binding activity in human bronchial epithelial cells, thereby promoting neutrophilic airway inflammation. 18 They also have chemoattractant properties towards immature dendritic cells, T cells and mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,41 We have demonstrated that HNPs at clinically relevant concentrations seen in the lung diseases can initiate inflammation by producing IL-8 and neutrophil migration, resulting in acute lung injury in vivo in mice. 33 Because HNPs are not direct chemoattractants for neutrophils, neutrophil infiltration is largely dependent on the release of IL-8 by lung epithelial cells in response to HNP stimulation. 42,43 Thus, an understanding of the mechanisms by which HNPs induce IL-8 production would provide potential therapeutic approaches to control inflammatory courses.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 To minimize variability from one patient to another, sputum was pooled from at least 20 patients with cystic fibrosis before purification. With respect to possible variability from one batch to another, at least 3 different batches of purified HNPs were used to stimulate cells in all experiments reported in the present study.…”
Section: Source Of Hnpsmentioning
confidence: 99%
See 1 more Smart Citation